Periodic solutions for second-order even and noneven Hamiltonian systems - Juan Xiao; Xueting Chen (Boundary Value Problems, 2024)
Abstract In this paper, we consider the second-order Hamiltonian system x ¨ + V ′ ( x ) = 0 , x ∈ R N . $$ \ddot{x}+V^{′}(x)=0,\quad x\in \mathbb{R}^{N}. $$ We use the monotonicity assumption introduced by Bartsch and Mederski (Arch. Ration. Mech. Anal. 215:283–306, 2015). When V is even, we can release the strict convexity hypothesis, which is used by Bartsch and Mederski combined with the monotonicity assumption. When V is noneven, we weaken the strict convexity assumption and introduce another hypothesis (see (V10)). Then in both cases, we can build the homomorphism between the Nehari manifold and the unit sphere of some suitable space. Using the Nehari manifold method introduced by Szulkin (J. Funct. Anal. 257:3802–3822 2009), we prove the existence of T-periodic solutions with minimal period T.